Cognitive and adaptive functioning outcomes after cancer diagnosis in early childhood: A systematic review - Jessica Beamish; Josephine Drijver; Marita Partanen (EJC Paediatric Oncology)
Objectives: About one quarter of children who are diagnosed with cancer are under four years old, which is a uniquely critical period in neurodevelopment. Younger age at diagnosis is a known risk factor for poorer long-term cognitive and functional outcomes, indicating that the combined impact of cancer and treatment may disproportionally affect this age group. To date, synthesis of the literature in this area has been limited by heterogeneous findings and methodologies. To help guide clinical practice and future research, this review aimed to describe the cognitive and adaptive functioning outcomes of young children with cancer, as well as summarise the impact of risk factors. Methods: We conducted a systematic review, according to PRISMA guidelines, of cognitive and adaptive functioning outcomes in cancer patients who were younger than four years at diagnosis. We searched PubMed, EMBASE and PsycINFO and included relevant articles. This review was registered in PROSPERO [CRD42024502629]. Results: There were 5747 records retrieved, and 54 papers were included after full-text review, representing 8083 participants. Long-term impairments in the domains of processing speed, attention, executive and adaptive functioning were reported in brain tumour, haematological and solid tumour groups. Brain tumour survivors also show deficits in IQ. Cranial radiotherapy was the most consistently associated risk factor with poorer cognitive and adaptive functioning. Risk of bias analysis showed most studies were classified as ‘strong’ quality, but there was variability in study sample size and design. Conclusion: Children diagnosed with cancer in early childhood are at high risk of cognitive and adaptive functioning deficits, potentially reflecting diffuse neurodevelopmental injury. However, outcomes are highly variable, with limited understanding of risk factors beyond medical treatment. The results support the recommended guidelines for early neuropsychological monitoring for all diagnostic groups to identify vulnerable patients and to implement timely interventions.